Occurrence of arbuscular mycorrhizae and bacterium Acetobacter diazotrophicus in sugar cane - Reis, Verônica Massena; Paula, Mauro Augusto de; Dobereiner, Johanna (Pesquisa Agropecuaria Brasileira, 1999)
The occurrence and distribution of species of arbuscular mycorrhizae fungi and Acetobacter diazotrophicus in sugar cane (Saccharum officinarum) grown in different regimes of crop management in the States of Rio de Janeiro and Pernambuco, Brazil, were studied. Thirty five samples of the rhizosphere soil and roots were collected from 14 varieties of sugar cane for the extraction of spores and isolation of the bacterium. The number of spores varied from 18 to 2,070 per 100 mL of soil, and the greatest diversity of fungal species was found in the sugarcane fields of Campos (Rio de Janeiro State), especially in those where the sugarcane trash was not burned at harvest. The predominant species found in the three localities sampled were: Scutellospora heterogama, Glomus etunicatum, Glomus occultum, Acaulospora sp. and Gigaspora margarita. A. diazotrophicus was present in almost all samples of root with the exception of one harvest of sugar cane taken from an area used for the sedimentation of vinasse (distillery waste). It was not possible to detect the bacterium from surface sterilized spores of native arbuscular mycorrhizal fungi (AMF), only from washed ones using sterile water.